TRACING THE ORIGIN OF JHAROKHA WINDOW USED IN INDIAN SUBCONTINENT - Zulfiqar, Zain (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2018)
The Jharokha is a distinctive feature of the architecture of Indian Sub-continent of medieval times. The study of the built heritage features is a way to discover and know about the old culture and society. A Jharokha is an oriel window projecting from upper storeys of a building used in medieval Indian architecture. Jharokha window projecting from the wall face of the building in an upper storey overlooking a street, market or any other open space. This study aims to trace the origin of traditional Jharokha window used in Indian subcontinent. In order to do it, the available data and literature have been carefully reviewed and studied to draw inferences. This study shows that the trend of a protruding window similar to Jharokhas seems to be present in different regions with their regional architectural flavor. The Indian architecture has influenced by various empires, and a lot of external influences came to this region because of the trade route. The external and regional influences have been studied to investigate the Jharokha window origin and form. The 3rd century BC balconies in Mauriyan Empire seems to amalgamate with the windows of Islamic architecture and developed finally into a local window form in the shape of Jharokha. The style and features of Jharokha vary concerning the local material and techniques available. The different era and different regions adopted this window form according to their own needs and aesthetics.